B0 and B1 Inhomogeneities in the Liver at 1.5T and 3.0T - Roberts, Nathan T (Magn Reson Med, 2020)
PURPOSE: The purpose of this work is to characterize the magnitude and variability of B0 and B1 inhomogeneities in the liver in large cohorts of patients at both 1.5T and 3.0T. METHODS: Volumetric B0 and B1 maps were acquired over the liver of patients presenting for routine abdominal MRI. Regions of interest were drawn in the nine Couinaud segments of the liver and the average value was recorded. Magnitude and variation of measured averages in each segment were reported across all patients. RESULTS: A total of 316 B0 maps and 314 B1 maps, acquired at 1.5T and 3.0T on a variety of GE Healthcare MRI systems in 630 unique exams, were identified, analyzed, and, in the interest of reproducible research, de-identified and made public. Measured B0 inhomogeneities ranged (5th-95th percentiles) from −31.7Hz to 164.0Hz for 3.0T (−14.5Hz to 81.3Hz at 1.5T), while measured B1 inhomogeneities (ratio of actual over prescribed flip angle) ranged from 0.59 to 1.13 for 3.0T (0.83 to 1.11 at 1.5T). CONCLUSION: This study provides robust characterization of B0 and B1 inhomogeneities in the liver to guide the development of imaging applications and protocols. Field strength, bore diameter, and sex were determined to be statistically significant effects for both B0 and B1 uniformity. Typical clinical liver imaging at 3.0T should expect B0 inhomogeneities ranging from approximately −100Hz to 250Hz (−50Hz to 150Hz at 1.5T) and B1 inhomogeneities ranging from approximately 0.4 to 1.3 (0.7 to 1.2 at 1.5T).